Knowledge management by farmers in the win-win relationship project in land Reform areas, Northern Thailand - Wallratat Intaruccomporn (2019)
© IEOM Society International. From research findings, it was found that knowledge level had a relationship with knowledge management in rice planting of farmers, but age, educational level, paddy farm size, farm income from rice, rice planting experiences, training experience and extension contact had no relationship with knowledge management on rice planting at all. From a comparative study, it was found that there was no difference in farmers' knowledge in each Sub-district. Nakornchum Sub-district had total average knowledge score higher than that in Baankaeng Sub-district and Mae Koa Tom Sub-district. From the comparison of farmers' knowledge management between each Sub-district, it was found that there was no difference at all. Problems and obstacles of farmers were the high cost of production leading to the loss of profit, therefore the farmers were in need of training on using fertilizers, "Good Agricultural Practice" (GAP) in planting organic rice, plant protection to increase yield per rai and the use of bio-extract products in the paddy fields in order to reduce production costs. Also, to increase good quality products which will have higher income than present.